A small library crRNA-enhanced CRISPR-Cas12a system for ultrasensitive point-of-care test of hantavirus M gene - Jian Zhou; Xue-mei Ren; Xin Wang; Pu Xu; Zhuo Li (Sensing and Bio-Sensing Research)
The integration of CRISPR-Cas systems with isothermal nucleic acid amplification (INA) holds transformative potential for point-of-care diagnostics, yet technical challenges such as limited sensitivity, cross-contamination risks, and incompatibility between amplification and detection phases hinder their clinical adoption. Here, we present a novel small library CRISPR/Cas12a crRNA (SLCC) platform for ultrasensitive detection of the hantavirus M gene, a conserved target critical for diagnosing hemorrhagic fever with renal syndrome (HFRS). The SLCC platform incorporates three key innovations: machine learning-guided crRNA design to target highly conserved viral regions; multi-crRNA collaborative signal amplification to enhance Cas12a's collateral cleavage activity, and a single-tube workflow integrating reverse transcription, recombinase polymerase amplification (RT-RPA), and CRISPR detection. Experimental validation demonstrated that the combinatorial six-crRNA strategy achieved an 85-fold improvement in sensitivity over single-crRNA systems (limit of detection (LoD): 0.086 pM vs. 7.31 pM for DNA of amplification). The optimized one-step RT-RPA/CRISPR-Cas12a workflow reduced assay time, while maintaining high specificity, as evidenced by concordant results with clinical samples and negligible cross-reactivity against SARS-CoV-2, HBV, and mycoplasma pneumoniae. Notably, the platform achieved a 42.29-fold lower LoD for RNA detection compared to single-crRNA CRISPR-Cas system, with fluorescence signal amplification plateauing within 45 min. The SLCCA platform integration of RNA reverse transcription amplification and Cas12a enzymatic cleavage within a single-tube workflow, combined with lateral flow strip-based signal readout, which achieves a sensitivity of 500 pM for RNA detection, demonstrating a 10–20-fold enhancement in the LoD compared to single-crRNA systems CRISPR-Cas diagnostic approaches. The advancements in the small library crRNA strategy address critical barriers in CRISPR-based diagnostics by offering a convenient and field-deployable solution for rapid, highly sensitive pathogen detection in resource-limited settings. This study establishes SLCC as a versatile framework that can adapt to emerging infectious disease surveillance and point-of-care applications.